ANTHROPOMETRY, EARLY LIFE ENVIRONMENT, AND COGNITION AMONG OLDER JAPANESE AMERICAN MEN. (11th November 2018) - Tom, S; Crane, P; Zhao, C; Gutierrez, J; White, L
Abstract: Few studies have examined socioeconomic environment underlying the association between small stature and poor cognitive in older adulthood. In a cohort where immigration to the US from Japan denotes a harsh inter-war early life environment, we hypothesized that 1) immigration status partially explains the association between smaller anthropometric measures and poor cognition; 2) education mediates these associations. The Honolulu Asia Aging Study included 3743 men of Japanese descent age 71 – 93 years in 1991–1993. Height, leg length, head circumference, and arm span were measured and years of education and immigration status were reported. Respondents completed the Cognitive Abilities Screening Instrument (range 0 – 100; ≤ 82 denotes impairment). For each anthropometric measure we ran separate series of nested ordinary least squares models adjusting for age only, then additionally for immigration status. We finally included education to test for mediation. Approximately 14% of respondents were born in Japan. Those in the shortest quarter (coefficient -4.33, 95% CI -5.74, -2.94) and second shortest quarter of height (coefficient -2.46, 95% CI -3.97, -0.95) had lower cognition, compared to those in the tallest quarter, adjusting for age. Associations between leg length and cognition were similar and were more modest for head circumference. These associations remained after adjusting for immigration status and were partially mediated by education. In older Japanese American men born near the turn of the 20th century, anthropometry may represent aspects of early life development more nuanced than societal-level socioeconomic environment that relate to later life cognition through pathways including education.